Professional Staff Competency on Domestic Water Supply Projects Sustainability in Tanzania - Chindengwike, James (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aimed to assess the influence of professional staff competency on domestic water supply projects sustainability in Tanzania: A case of Singida District. Survey research design was adopted whereby a simple random sampling was used to collect information from 100 officials who are the part of the management. Questionnaire and documentary review were used as data collection methods whereas descriptive and inferential statistics were used in analyzing the collected data by using SPSS. Finding of this study show that groups with good and average managerial skills had 2.256 and 1.75 respectively times-more likely their domestic water to be sustainable compared to those groups with poor managerial skills. The finding also revealed that those groups with good and average management knowledge had 1.613 and 1.209 times-more likely their domestic water to be sustainable compared to those with poor management knowledge and managerial skills respectively. Based on the findings, this study recommended that, the government should comprehensively employ people with water management knowledge, and by taking into consideration the experience and technical efficiency as it holds positive influence on sustainability of water projects. Also, regular training of the water management staff for capacity building is enormously essential for sustainability and development of projects. This can be done through setting proper budget in the particular water project area.